Pre-Hospital Emergency Medical Services: An Epidemiological Survey in Mashhad, Iran - Mohsen Seyyednozadi; Lida Jarahi; Majid Reza Erfanian; Mohammad Taghi Shakeri (Patient Safety and Quality Improvement Journal, 2017)
Introduction: Providing appropriate care, in the right place and at the right time, is the main goal of emergency medical services (EMS) to save lives. The present study aimed to assess the pre-hospital EMS in Mashhad, the second largest metropolis in Iran. Materials and Methods: In this research, data were extracted from the pre-hospital emergency mission forms, which were collected from the EMS stations in Mashhad and suburbs through systematic random sampling. In addition, supplementary information was obtained from the ambulance dispatch cards and emergency communication center forms. Results:Automobile accidents (33.7%) and cardiovascular events (17.8%) were the most common causes of contacts to the EMS. In the city and road stations, the mean response time was 2.6 and 1.6 minutes, while the mean time of arrival at the scene was 13.2 and 11.4 minutes, and the mean evacuation time was 13.2 and 11.4 minutes, respectively. Individuals aged 20-29 (25.2%) and more than 60 years (23.9%) constituted the majority of the cases receiving EMS. Conclusion: According to the results, the ‘golden time’ for emergency care was of great importance in the patients injured in car accidents or affected by cardiovascular events. Furthermore, a significant difference was observed in the time indices of EMS in Mashhad city with the EMS standards due to the lack of human resources or EMS facilities. Some contacts to the EMS were unnecessary, and no expert team aid was needed in some cases. It is recommended that citizens be trained on solving the problems associated with road traffic by implementing mobile emergency, while transfer units must be established for the better provision of emergency care by the EMS in Mashhad.